Control of Audiences through Information Communication Technology in the Perspective of Communication Psychology - Syafrizaldi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This journal discusses audience control through information and communication technology in the perspective of communication psychology through studying phenomena with a literature approach. Information and communication technology (ICT) is capable of providing a controlling effect for individuals and society. In fact, from 2014-2019 there were mass actions carried out by a group of masses. Some have named it the MUI Fatwa Guard National Movement (GNPF-MUI) Action 411 and 212 until the mass action which took place on May 22, 2019 and on September 26, 2019. Various news has spread through the sophistication of information and communication technology through media applications social facebook, instagram, whatsapp information spreads so massively. This has an effect on controlling the behavior of individuals and communities (audiences), so that so many audiences who are exposed to information are unable to stem and carry out searches related to the information obtained, resulting in behavior in accordance with the expectations of the information disseminators. In this case it can be concluded that the effect of media can affect perceptions, down to the aspects of affection and behavior. Communication psychology provides a relevant understanding perspective related to these various phenomena. Individuals and societies when using information and communication technology involve perceptions, memories, needs, values, attitudes, motives, motivations, personality, knowledge, emotions, skills and personal and social interpretations. Thus it can be concluded that information and communication technology in use today can have an impact on audiences in aspects of perception, affection, and behavior. So without realizing it information technology can be used for the benefit of various individuals or groups in controlling audiences.